An Overview on Fault Management for Electric Vehicle Onboard Chargers - Luis-Fernando Gaona-Cárdenas; Nimrod Vázquez-Nava; Ruiz Martínez, Omar Fernando; Alejandro Espinosa-Calderón; Alejandro-Israel Barranco-Gutiérrez; Rodríguez Licea, Martín Antonio (My University, 2022)
Onboard charging systems (OBCs) convert AC power from an external charging source into a DC voltage used to charge the battery pack of an electric vehicle (EV). OBCs are versatile since they can convert energy from almost every AC source, including standard household electrical receptacles, without needing wall chargers or charging stations. Since the same motor-drive electronics are reconfigured for onboard charging, weight and cost barely increase. However, the power quality and reliability of the OBCs are essential elements for proper grid interconnection. This article reviews the failures of power electronic converters that can be used for onboard charging and their most prominent fault-tolerance techniques. The various fault-tolerance methods are evaluated and compared in terms of complexity, cost, and performance to provide insights for future developments and research directions.